Th2 and metabolic responses to nematodes are independent of prolonged host microbiota abrogation. (24th November 2022) - Elizalde‐Velázquez, Luis E.; Yordanova, Ivet A.; Liublin, Wjatscheslaw; Adjah, Joshua; Leben, Ruth; Rausch, Sebastian; Niesner, Raluca; Hartmann, Susanne
Abstract: Antibiotic treatment can lead to elimination of both pathogenic bacteria and beneficial commensals, as well as to altered host immune responses. Here, we investigated the influence of prolonged antibiotic treatment (Abx) on effector, memory and recall Th2 immune responses during the primary infection, memory phase and secondary infection with the small intestinal nematode Heligmosomoides polygyrus . Abx treatment significantly reduced gut bacterial loads, but neither worm burdens, nor worm fecundity in primary infection were affected, only worm burdens in secondary infection were elevated in Abx treated mice. Abx mice displayed trends for elevated effector and memory Th2 responses during primary infection, but overall frequencies of Th2 cells in the siLP, PEC, mLN and in the spleen were similar between Abx treated and untreated groups. Gata3 + effector and memory Th2 cytokine responses also remained unimpaired by prolonged Abx treatment. Similarly, the energy production and defence mechanisms of the host tissue and the parasite depicted by NAD(P)H fluorescence lifetime imaging (FLIM) did not change by the prolonged use of antibiotics. We show evidence that the host Th2 response to intestinal nematodes, as well as host and parasite metabolic pathways are robust and remain unimpaired by host microbiota abrogation.